Determinants of Investment Opportunity Set (Degree of Internationalization and Macroeconomic Variables) - Cynthia utama; Meiti Sulistika (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2015)
The aim of this study is to investigate the influence of internal factors (i.e. the degree of internationalization, profitability, firm size, and financial leverage) and external factors (i.e. GNP growth and the inflation rate) on firms’ growth opportunities or their Investment Opportunity Set (IOS). The IOS is measured by the market-to-book assets ratio. The result shows that profitability and firms’ size have a positive impact on the IOS whereas the degree of internationalization and financial leverage has a negative influence on the IOS. Finally, the IOS is positively affected by GNP growth while the inflation rate has a negative impact on IOS.